The Effect of Positive Habituation on Early Childhood Social-Emotional Skills: Systematic Literature Review - Sayuti, Zulfa Mujahidah; Ayuningtyas, Fadilla (Jurnal Pendidikan Raudhatul Athfal, 2024)
Early childhood social-emotional development is an important aspect in supporting optimal growth and development. This article aims to examine the influence of positive habituation on early childhood social-emotional skills through the Systematic Literature Review (SLR) approach. The review process involves sifting through the literature from 5,760 articles to produce 4 relevant articles. The results of the study showed that positive habits, such as sharing, waiting for turns, and collaboration, played a significant role in improving children's social-emotional skills, including self-regulation, empathy, and social interaction. In addition, the synergy between parents, teachers, and the environment supports the success of this habituation program. Barriers such as parenting inconsistencies and lack of parental understanding were also identified as major challenges. These findings confirm that positive habituation is a long-term investment that has an impact on children's social, academic, and professional success in the future.